Best available techniques for the waste water treatment - Yodchyk, Anna V.; Dubianok, Sniazhana A. (Journal of the Belarusian State University. Ecology, 2021)
The necessity of the implementation of the Best available Techniques by nature users determined In the environmental legislation of the Republic of Belarus. The article provides general information on the best available techniques (BAT) and the reasons for their implementation in the Republic of Belarus. Trends in the flow of pollutants as part of waste water into surface water bodies of the country have been analyzed in the context of the main pollutants and types of economic activities of enterprises that discharge the pollutants. Priority factors have been determined when choosing a wastewater treatment technology and a treatment method within the framework of the selected technology.
Keywords: best available techniques; waste water; pollutant; surface water body